Microstructure study of cold rolling nanosized in-situ TiB2 particle reinforced Al composites. (15th September 2017) - Dan, C.Y.; Chen, Z.; Ji, G.; Zhong, S.H.; Wu, Y.; Brisset, F.; Wang, H.W.; Ji, V.
Abstract: Nanosized TiB2 particle reinforced Al matrix composites, cold-rolled at the true strain levels in the range from 0.9 to 3.0, were characterized by scanning electron microscopy (SEM) and electron backscatter diffraction (SEM/EBSD) and transmission electron microscopy (TEM) in order to examine microstructure evolution associated with the different deformed states. Two types of TiB2 particle-distributions were observed, the majority of TiB2 reinforcement particles were agglomerated along the grain boundaries forming particle-clusters and the rest was dispersed inside the grains. The TiB2 particle-clusters were found to improve local grain refinement by locally increasing the density of high angle grain boundaries (HAGBs). The small submicrometer sized Al grains were observed next to the TiB2 particle-clusters in which dynamic recrystallization mechanism was partially promoted. On the contrary, the presence of the fine TiB2 particles within the primary coarse Al grains generally led to the reduction of HAGBs by hindering the generation of dislocation cell structures and microshear bands during deformation. Graphical abstract: Highlights: Nanosized TiB2 particle reinforced Al matrix composites are cold rolled at different strain levels. Microstructure evolution associated with the two different distributions of TiB2 nanoparticles has been characterized. TiB2 nanoparticle-clusters along Al grain boundaries result in local grain refinement and dynamic recrystallization. Alternatively, TiB2 nanoparticles dispersed in Al matrix delay the generation of new high angle grain boundaries.